Association of waist circumference and health risk factors among faculty members of a Philippine university - Talavera, Theresa M.; Atienza, Liezl M.; Barba, Corazon VC.; Padilla, Lowela M.; Africa, Leila S. (2011)
According to the World Health Organization (2000), obesity is linked with the increasing trend in the prevalence of cardiovascular diseases (CVD) and diabetes mellitus (DM) in developed and developing countries.

In the Philippines, cardiovascular diseases such as hypertension and atherosclerosis remain to be the two leading causes of mortality. The study aimed to determined the relationship of waist circumference (WC) with health risk factors among faculty members of a Philippine university. Anthropometric, clinical, and biochemical examinations were conducted among 100 randomly selected members of the UP Los Banos faculty.

It was found that majority (57%) of the respondents had normal nutritional status, about one third (34%) was overweight, and 7% was found to be obese. Being overweight was more prevalent among mules whereas obesity was more common in females.

It was observed that majority of the respondents in both genders were in the pre-hypertensive stage, with relatively higher prevalence (66%) in males than in females (48%). Hypertension was found to be highly prevalent in both genders, 10% higher among men than women.

Among males, the results of the study corroborates previous findings that increased adiposity which is indicated by increasing waist circumference is associated with increasing fasting blood sugar, triglyceride, and blood pressure.

The significant association of WC with risk factors suggests that abdominal obesity may play an etiologic role in the clustering of health risk factors which is a clinical feature of the metabolic syndrome. Metabolic syndrome is operationally defined as clustering of high blood pressure, hyperglycemia, high triglycerides, low HDL-cholesterol and abdominal obesity (Dorairaj and Anand, 2004). The association of waist circumference with selected health risks factors may suggest that larger waist measurement as indicator of abdominal obesity may predict the development of CVD and DM.
Keywords: Health risk assessment; University faculty -- Health risk assessment